TINDAK KEKERASAN DALAM RUMAH TANGGA TERHADAP ISTRI MENURUT UNDANG – UNDANG NOMOR 23 TAHUN 2004 DAN MENURUT HUKUM ISLAM Suatu Tinjauan dari Sosiologi Hukum - Asmara Hadi (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2012)
EliminationActof Domestic Violenceand the Lawof Islamhavethe same spirit. Underlying thetwolawsisrespect forhuman dignity, to do withthe rights ofhusband and wifein the household, as well as themeaning ofviolenceordiscriminationagainst women. It's just thatthelawis clearaboutthe criminal provisions, while Islamic lawis notavailablefortheprovisionof criminalviolenceagainst the wifein the household